TUJUAN NEGARA DALAM ISLAM MENURUT YUSUF AL-QARADHAWI: The Purpose of the State in Islam According to Yusuf al-Qaradawi - Abdullah, Sigit Ridwan (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2017)
AbstractYusuf al-Qaradawi is one of the figures of so many scholars who contributed to the thinking of the Islamic state. His attention to politics and state is evidenced by the Â Â presence of some of his works such as Ø§Ù„Ø¥Ø³Ù„Ø§Ù… ÙÙŠ Ø§Ù„Ø¯ÙˆÙ„Ø© ÙÙ‚Ù‡ Ù…Ù† (Fiqh of State in Islamic Perspective), Â Ø§Ù„Ø´Ø±Ø¹ÙŠØ© Ø§Ù„Ø³ÙŠØ§Ø³Ø© (Political Sharia), Ø§Ù„Ø¥Ø³Ù„Ø§Ù… Ù…ÙˆØ§Ø¬Ù‡Ø© ÙÙŠ Ø§Ù„Ø¹Ù„Ù…Ø§Ù†ÙŠ Ø§Ù„ØªØ·Ø±Ù (Extreme Secular Attitudes towards Islam), ÙˆÙ‡Ù… Ù„Ø§ ØÙ‚ÙŠÙ‚Ø© Ø§Ù„Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ù„Ø£Ù…Ø© (The Political Unit of Ummah is a Reality). This research tried to review Yusuf al-Qaradawi's view on Islamic state, using descriptive analytical methods and literature review upon the above stated Yusuf al-Qaradawi's books or writings. The research result shows that Islamic state according to Yusuf al-Qaradawi is